2019
DOI: 10.1590/1678-4324-2019180345
|View full text |Cite
|
Sign up to set email alerts
|

A Histopathological, Immunohistochemical and Biochemical Investigation on the in vitro Antioxidant, Myeloprotective, Hematoprotective and Hepatoprotective Effects of Hypericum triquetrifolium Seed Extract Against Cyclophosphamide-Induced Toxicity

Abstract: The aim of this study was to investigate in vitro antioxidant properties and in vivo protective effects of the methanol extract of the Hypericum triquetrifolium Turra (HT) seed against acute hepatotoxicity, myelotoxicity and hematotoxicity in rats induced by cyclophosphamide (CP). In order to investigate in vivo protective effects of the HT extract on rat tissues, the rats were divided into nine groups. The toxic effects of CP and the protective effects of HT extract on nucleated cells that are produced by bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
(45 reference statements)
0
10
0
1
Order By: Relevance
“…In the present study, the bone marrow nucleated cell level demonstrated a statistically significant decrease in the group that was administered CPx compared to the control value. In a similar study, it was reported that CPx reduced bone marrow nucleated cell levels and caused myelotoxicity [26,40]. It was reported in a previous studies that CPx-induced myelosuppression / immunotoxicity limited the use of CPx [41,42].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the present study, the bone marrow nucleated cell level demonstrated a statistically significant decrease in the group that was administered CPx compared to the control value. In a similar study, it was reported that CPx reduced bone marrow nucleated cell levels and caused myelotoxicity [26,40]. It was reported in a previous studies that CPx-induced myelosuppression / immunotoxicity limited the use of CPx [41,42].…”
Section: Discussionmentioning
confidence: 78%
“…CPx, which has been known to be effective in the treatment of cancer and non-malignant diseases since 1958 and has a wide area of use in many neoplastic diseases as a standalone drug or in combination with other chemotherapeutics, also includes side-effects [25]. The fact that CPx causes multi-organ damage limits the effective high-dose use of the drug [26]. Hematopoietic depression is among the main side-effects of CPx.…”
Section: Introductionmentioning
confidence: 99%
“…The aerial parts of HT with methanolic extract possesses high antioxidant activities 23 which might be useful in protecting against or decelerating the development of diverse oxidative stress-induced disorders 24 . Thus, HT is a strong candidate to protect the healthy cells from the toxic side effects of CYP 25 .…”
Section: Cyclophosphamidementioning
confidence: 99%
“…(Matalon et al, 2004;Altaylý et al, 2012). CP, an alkylating chemotherapeutic drug, is metabolized by liver cytochrome P450 enzymes, namely CYP3A4 and CYP2B6 which demonstrate active therapeutic and cytotoxic metabolites and diffuse out of the hepatocytes into the plasma (Yildiz, et al, 2019). CP spreads throughout the body and generates two active metabolites: phosphoramide mustard (PAM) and acrolein (ACR).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it interacts with protein and causes changes in the structure and function of enzymes and harms the tissue antioxidant defense mechanism. CPinduced toxicity is a consequence of a mitochondrial dysfunction and ends with a decrease of adenosine triphosphate owing to nitrosative and oxidative stress (Yildiz, et al, 2019). Curcumin's biological activity is attributed to its bioavailability in humans.…”
Section: Introductionmentioning
confidence: 99%